Edukasi Bahaya Rokok dan Vape: Mengubah Persepsi Remaja dari Gaya Hidup Menjadi Ancaman Kesehatan di SMAN 1 Parepare - Nurussyariah Hammado; Paramita, Diah Astini; Nurul Mutiah Aminuddin; Rayhani Ichsan; Bhirau Wilaksono (MAMMIRI: JURNAL PENGABDIAN MASYARAKAT, 2025)
The prevalence of smoking and vaping among Indonesian adolescents continues to increase, driven by the misconception that these products represent a modern lifestyle rather than a serious health risk. School-based health education interventions are essential to address this issue. This community service program aimed to increase students' knowledge and awareness regarding the dangers of smoking and vaping at SMAN 1 Parepare. A participatory health education approach was implemented involving 43 participants. The intervention utilized poster media, peer education with university students as presenters, interactive discussions, and gamified quizzes. Evaluation was conducted through participant observation, active participation assessment, and post-education quiz. The retention rate reached 100% with no participant dropout. All participants engaged in the quiz session, and three students actively raised critical questions regarding smoking prevention strategies at school. The combination of peer education, visual media, and gamification effectively maintained participant engagement and facilitated knowledge transfer regarding smoking and vaping risks among adolescents.